Improvement of tribo-active behavior of g-C3N4 nanosheets using m-LaVO4 nanoparticles - Kavita; Singh A.K.; Shukla N.; Kumar B.; Verma D.K.; Maurya J.L.; Singh S.; Rastogi R.B. (My University, 2025)
The tribological properties of the graphitic carbon nitride (g-C3N4) nanosheets are far better than morphologically similar reduced graphene oxide. Further improvement of the tribological behavior of g-C3N4 nanosheet was intended by introducing lanthanum orthovanadate nanoparticles in the monoclinic phase (m-LaVO4). The HR-SEM and TEM/HR-TEM of the binary nanocomposite (g-C3N4/m-LaVO4) displayed dispersed m-LaVO4 nanoparticles throughout g-C3N4 nanosheets. The synthesized nano additives, nanosheets (g-C3N4), nanoparticles (m-LaVO4), and nanocomposite (g-C3N4/m-LaVO4) could be characterized using p-XRD and FT-IR. XPS analysis of the nanocomposite helped to determine the chemical states of elements. Tribological tests were carried out on a four-ball tester using ASTM D4172 and ASTM D5183 test conditions at 0.05 % w/v optimized concentration of the additives in paraffin oil (PO), which is 4–5 times lower than the available literature reports regarding nanocomposites of g-C3N4 nanosheets. The results revealed a significant decrease in friction/wear and a remarkable improvement in the load-bearing capacity of the nanocomposite as compared to g-C3N4 nanosheets and m-LaVO4 nanoparticles. The morphological examination of the worn steel surface through AFM and SEM supported the observed tribological data. EDX analysis of the tribofilm verified the elemental composition, whereas the XPS yielded the chemical states of the constituent elements. The highly advanced tribological activity of the nanocomposite has been ascribed to the synergy between noncovalently interacting nanoparticles (m-LaVO4) and nanosheets (g-C3N4). The possible lubrication mechanism has also been depicted. © 2023 Elsevier B.V.